The impact of protest responses in choice experiments - Melina Barrio; Maria L. Loureiro (Fondazione Eni Enrico Mattei (FEEM), 2010)
Not much attention has been given to protest responses in choice experiments (CE). Using follow-up statements, we are able to identify protest responses and compute welfare estimates with and without the inclusion of such protest responses. We conclude that protest responses are fairly common in CE, and their analysis affects the statistical performance of the empirical models. In particular, when the sample is corrected by protests, our results come from utility consistent models. Thus, future choice experiments should consider the role of protest responses as contingent valuation studies have done.
Keywords: Q01; Q10; Q50; 330; Protest Responses; Choice Experiments